DESIGN OF AUTOCLAVE FOR FRESH SHRIMP STERILIZATON PROCESS USING FINITE ELEMENT ANALYSIS - Chandra, Hendri; Abdi, Jusran; Homzah, Ozkar F.; Basri, Hasan; Azhari, Ikbal; Utami, Nurhabibah Paramitha Eka (AUSTENIT, 2022)
Chloramphenicol is one of antibiotic compound which is an additional ingredient that is forbidden to be used in food products, especially in fresh shrimp product export. To avoid the used of preservative, then required sterilization process in a physical way which is vaporization using a high-pressure supercritical carbon dioxide (CO2). One of sterilization process for supercritical carbon dioxide is using autoclave media. Autoclave is a closed heating device used to sterilize or reducing a substance or object that is disserve by using high temperature and high pressure steam. In designing and constructing autoclave, the first step to be done is to define the function and the operation capacity. The function and capacity will determine the initial dimension of autoclave as well its working pressure and temperature. In this study, the autoclave was designed with quantitative methods and modeling using software Autodesk inventor 2016 based on finite element method. The given load is in the form of supercritical carbon dioxide pressure of 73.83bar and temperature of 31.30C. Based on the result of design, quantitative methods gives the safe result and optimized thickness needed autoclave usage.